Socially Shared Metacognitive Regulation in Asynchronous CSCL in Science: Functions, Evolution and Participation - Tuike Iiskala; Simone Volet; Erno Lehtinen; Marja Vauras (EARLI, 2015)
The significance of socially shared metacognitive regulation (SSMR) in collaborative learning is gaining momentum. To date, however, there is still a paucity of research of how SSMR is manifested in asynchronous computer-supported collaborative learning (CSCL), and hardly any systematic investigation of SSMR's functions and evolution across different phases of complex collaborative learning activities. Furthermore, how individual students influence group regulatory effort is not well known and even less how they participate in SSMR over the entire collaborative learning process. The multi-method, in-depth case study presented in this article addresses these gaps by scrutinizing the participation of a small group of students in SSMR in asynchronous computer supported collaborative inquiry learning. The networked discussion, consisting of 640 notes, was used as baseline data. The sets of notes, which formed nine SSMR threads, were identified and their functions analyzed. Several analytical methods, including social network analysis, were used to investigate various aspects of individual participation. The findings show that some SSMR threads lasted over an extended period, and they sometimes intertwined or overlapped. Furthermore, SSMR threads were found to play different functions, mainly inhibiting the perceived inappropriate direction of the ongoing cognitive process. Finally, SSMR was found in all phases of the process - but with some variation. The use of different analytical methods was critical as this provided a variety of complementary insights into students' participation in SSMR. The value of using multiple, rigorous analytical methods to understand SSMR's significance over the entire course of an asynchronous CSCL activity is discussed.